2012
DOI: 10.3390/agriculture2040295
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Sterility—A Promising Approach to Gene Confinement and Breeding for Genetically Modified Bioenergy Crops

Abstract: Advanced genetic and biotechnology tools will be required to realize the full potential of food and bioenergy crops. Given current regulatory concerns, many transgenic traits might never be deregulated for commercial release without a robust gene confinement strategy in place. The potential for transgene flow from genetically modified (GM) crops is widely known. Pollen-mediated transfer is a major component of gene flow in flowering plants and therefore a potential avenue for the escape of transgenes from GM c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Using this approach, barnase has been used for male sterile plant production in several monocot species including wheat (Triticum aestivum L.) [35], creeping bentgrass (Agrostis stolonifera L.) [36], and rice (Oryza sativa L.) [37]. In wheat, tapetum-specific promoters ca55 (derived from maize (Zea mays L.)), and T72 and E1 (derived from rice) were used to drive barnase expression [35].…”
Section: Barnase-induced Male Sterilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Using this approach, barnase has been used for male sterile plant production in several monocot species including wheat (Triticum aestivum L.) [35], creeping bentgrass (Agrostis stolonifera L.) [36], and rice (Oryza sativa L.) [37]. In wheat, tapetum-specific promoters ca55 (derived from maize (Zea mays L.)), and T72 and E1 (derived from rice) were used to drive barnase expression [35].…”
Section: Barnase-induced Male Sterilitymentioning
confidence: 99%
“…No off-target expression was reported, and the male sterile phenotype was stably inherited in progeny when backcrossed to nontransgenic creeping bentgrass. When barnase was expressed in rice using the pollenspecific promoter Zm13 (derived from maize) [37], transgenic events were crossed to nontransgenic rice. The resulting progeny produced 50% viable nontransgenic pollen.…”
Section: Barnase-induced Male Sterilitymentioning
confidence: 99%
“…Moreover, the Zm13 is a pollen-specific gene in maize that is expressed in the late stages of pollen development. Fusing the promoter of Zm13 ( Zm13pro ) with the cytotoxic BARNASE gene and transforming into japonica rice background displayed stable male sterility, which indicates the stable expression of the transgene ( Hague et al, 2012 ). Similarly, the gene BoA9 (from Brassica oleracea L.) is a tapetum-specific promoter that is responsible for male fertility.…”
Section: Biotechnological Strategies To Develop Male Sterility and Hymentioning
confidence: 99%
“…Recently, Hague et al . () demonstrated that the Zm13 promoter can drive pollen‐specific expression of the cytotoxic gene barnase in stably transformed rice, resulting in plants with pollen sterility. As it is pollen‐specific and inherited as a single Mendelian trait, pollen sterility could be an effective strategy for gametophytic transgene confinement but it would not be effective against transgene escape through seed scatter and vegetative propagation.…”
Section: Rationales Behind Gurtsmentioning
confidence: 99%